Quantitative resistance to bacterial pathogens of rice - Leach, Jan E.; Bossa Castro, Ana M.; Huerta, Alejandra I.; Delorean, Emily E.; Raghavan, Chitra; Tekete, Cheick; Dereeper, Alexis; Tonnessen, Bradley W.; Koita, Ousmane; Mosquera Cifuentes, Gloria Maria; Leung, Hei; Verdier, Valerie M. (2018)
Disease resistance is the foundation for managing many plant diseases, because resistant varieties have the strongest impact with minimal environmental effects or cost. Consequently, sources of broad-spectrum resistance (BSR), or resistance that is effective against multiple and/or diverse pathogens is of particular interest. However, achieving BSR depends on having effective resistance sources to introgress into elite germplasm. Multi-parent Advanced Generation Inter-Cross (MAGIC) populations are powerful tools for identifying resistance because they have high levels of recombination and enhanced resolution relative to biparental populations. We screened an indica rice MAGIC population developed from eight elite founders for BSR to diverse strains of the rice bacterial blight and leaf streak pathogens Xanthomonas oryzae pv. oryzae (Xoo) and X. o. pv. oryzicola (Xoc), respectively. In addition, building on our hypothesis that durable disease resistance is attainable by targeting key microbial virulence factors, we screened for resistance to Xoo strains isogenic for the known and common virulence factor TAL7b. A combination of genome-wide association studies and interval mapping analyses revealed a number of loci that conferred BSR to both Xoo and Xoc, as well as resistance targeted at TAL7b. These BSR QTL are excellent sources for durable, broadly effective resistance in the field.